An e-learning Environment for Influencing Children’s Attitudes Toward Ultraviolet Protection - Theodosi, Sotiroula; Nicolaidou, Iolie (My University, 2022)
This paper describes a work in progress to design and evaluate an e-learning intervention that utilizes the Internet of Things (IoT) to increase awareness of the dangers of ultraviolet (UV) radiation exposure and promote sun protection practices early in life. The authors' previous work in a pre-test post-test control group study (Study 1) involved children in using IoT devices to collect and analyze real-time UV radiation data. Preliminary data were promising in this small-scale study, but the latter did not use a validated instrument to measure children's UV knowledge, attitudes, and behaviors. This second study has a dual aim. First, it reports on the results of a systematic literature review that aimed to identify validated questionnaires that a) measure attitudes toward UV light protection, b) are appropriate for primary school, and c) are suitable for evaluating e-learning prevention interventions if they are used as a pre-test and post-test. Second, it describes how the intervention of Study 1 will be re-enacted through an e-learning platform that allows for deepening student understanding and engagement through gamification and allows for visualizing students' understanding in real-time.
Keywords: e-Learning Environment; Ultraviolet (UV) Protection; Systematic Literature Review; Children; Attitudes; Validated Instruments